2006
DOI: 10.1038/sj.ijir.3901525
|View full text |Cite
|
Sign up to set email alerts
|

Do vardenafil and tadalafil have advantages over sildenafil in the treatment of erectile dysfunction?

Abstract: Erectile dysfunction (ED) affects up to 50% of men between the ages of 40 and 70 years of age. Sildenafil, vardenafil and tadalafil have all been shown to be similarly effective in the treatment of men with ED of vary etiologies, to have similar adverse effects profiles, and to improve quality-oflife by similar amounts. As these phosphodiesterase 5 (PDE5) inhibitors all increase the hypotensive effects of nitrates, they are not suitable for use in patients taking nitrates for the treatment of ischaemic heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 154 publications
(212 reference statements)
0
22
0
Order By: Relevance
“…These inhibitors also have the same target and interact with many of the same residues at the active site of PDE5, as shown by the crystal structures of the isolated PDE5 catalytic domain in complex with silde-nafil and vardenafil (Sung et al, 2003;Card et al, 2004;Huai et al, 2004;Zhang et al, 2004;Wang et al, 2006). Although the head-to-head comparison is still lacking, the pharmacokinetic and pharmacodynamic analyses showed that these PDE5 inhibitors have similar efficacy and tolerance but exhibit some functional differences both in vitro and in vivo (Briganti et al, 2005;Shabsigh et al, 2006;Supuran et al, 2006;Wright, 2006;Doggrell, 2007;Mehrotra et al, 2007). For example, vardenafil shows 10-to 40-fold tighter binding with PDE5 than sildenafil and has an area under the curve of 74.5 g ⅐ h/liter at a 20-mg dosage compared with 1965 for sildenafil at a 100-mg dosage (Shabsigh et al, 2006;Mehrotra et al, 2007).…”
mentioning
confidence: 99%
“…These inhibitors also have the same target and interact with many of the same residues at the active site of PDE5, as shown by the crystal structures of the isolated PDE5 catalytic domain in complex with silde-nafil and vardenafil (Sung et al, 2003;Card et al, 2004;Huai et al, 2004;Zhang et al, 2004;Wang et al, 2006). Although the head-to-head comparison is still lacking, the pharmacokinetic and pharmacodynamic analyses showed that these PDE5 inhibitors have similar efficacy and tolerance but exhibit some functional differences both in vitro and in vivo (Briganti et al, 2005;Shabsigh et al, 2006;Supuran et al, 2006;Wright, 2006;Doggrell, 2007;Mehrotra et al, 2007). For example, vardenafil shows 10-to 40-fold tighter binding with PDE5 than sildenafil and has an area under the curve of 74.5 g ⅐ h/liter at a 20-mg dosage compared with 1965 for sildenafil at a 100-mg dosage (Shabsigh et al, 2006;Mehrotra et al, 2007).…”
mentioning
confidence: 99%
“…1). 1,2) cGMP level is important for the maintenance of erection because, together with nitric oxide (NO), it is involved in the relaxation of the smooth muscles of the corpus cavernosum. Udenafil (Zydena ® ), currently marketed in Korea, was developed by Dong-A Pharmaceutical Co. (Yongin, South Korea) for oral administration to male patients suffering from erectile dysfunction.…”
mentioning
confidence: 99%
“…the three FDa-approved PDe5 inhibitors have been shown to be similarly effective in the treatment of eD. 77 there have been no trials comparing potential differences in treatment success after rP. reviews Sildenafil a few studies investigating the rehabilitative impact of sildenafil treatment after unilateral or bilateral nerve-sparing rP have been performed, and only one double-blind, randomized, placebo-controlled trial.…”
Section: Phosphodiesterase Type 5 Inhibitorsmentioning
confidence: 98%